Effect of Whitening dentifrice on discoloration of tooth surface: an updated systematic review and meta-analysis - Samira Hajisadeghi; Mohsen Khansari; Mohsen Yazdanian; Elham Keykha (BMC Oral Health)
Abstract Tooth discoloration is a common cosmetic concern, often addressed using whitening dentifrices (WDFs). This updated systematic review and meta-analysis aimed to assess the effectiveness of WDFs in decreasing tooth surface discoloration compared to regular dentifrices (RDFs). A comprehensive search of multiple electronic databases identified 14 randomized controlled trials (RCTs) meeting the inclusion criteria. The meta-analysis showed that WDFs significantly reduced both the area and intensity of stains, with 94.45% and 77.78% efficacy, respectively. Studies incorporating adjunctive chemical agents in WDFs showed enhanced stain reduction. Despite significant heterogeneity (I2 = 91%) among the studies, the results consistently favored WDFs over RDFs. Low publication bias was detected, and sensitivity analyses confirmed the robustness of the findings. These results endorse the utilization of WDFs for managing extrinsic tooth stains, though further research is needed to standardize methodologies and assess long-term effects.